Adopting the stranger as kindred in Deuteronomy - Glanville, Mark (Ancient Israel and its literature, 2018)
Review of the scholarship and methodology -- GR: cognates and use in other texts -- The gēr in social law -- The gēr in law of judicial procedure -- The gēr in Deuteronomy's feasts -- The gēr in Deuteronomy's framework (Deut 1-12, 27-34)